Influence of Anodizing Parameters on Surface Hardness of Recast Al6061 for Hexapod Fixator Ring Development - Firdaus, Iffa Azzahra; Priadythama , Ilham; Setyanto, R Hari (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
Blount’s disease can potentially reduce the productivity of the next generation. An external fixation device, such as a hexapod, is required to manage this disease. However, a hexapod is still difficult to access at an affordable price. Gravity casting is an alternative manufacturing process that can potentially reduce the cost of a hexapod, especially its ring component. However, it might face issues related to surface quality and potential defects. Anodizing can enhance the surface protection and mechanical strength of components, but studies on the anodizing of cast surfaces remain limited. This study aims to determine the effects of current density (2, 2.5, and 3 A/dm2) and anodizing time (10, 15, and 20 minutes) on the hardness and characteristics of the oxide layer on hexapod ring surfaces made from re-cast aluminum 6061. The results indicate that anodizing at 2.5 A/dm2 for 20 minutes produces an oxide layer with the highest hardness value.